BS ISO 19587. Fine ceramics (advanced ceramics, advanced technical ceramics). Mechanical properties of ceramic composites at elevated temperature in air atmospheric pressure. Determination of in-plane shear strength. (21st May 2020) - British Standards Institution,
No abstract available